Sonication increases the porosity of uncooked rice kernels affording softer textural properties, loss of intrinsic nutrients and increased uptake capacity during fortification - Bonto, Aldrin P.; Tiozon, Rhowell N.; Rojviriya, Catleya; Sreenivasulu, Nese; Camacho, Drexel H. (Elsevier, 2020)
This work investigates the effect of sonication on brown and milled rice grains of both waxy and non-waxy varieties. We report herein the microstructural analysis of uncooked rice kernels under sonication and its effect on the textural properties. X-ray computed tomography results showed the formation of microporous surfaces and the creation of cracks and fissures. Sonication increased the % porosity of the rice samples allowing for easy penetration of water during the cooking process and promotes softer texture. Moreover, the effect of sonication in brown rice resulted to the decrease in endogenous iron and phosphorus contents but increased its capacity for iron uptake through fortification when sonicated rice is soaked in the mineral solution.